#### Answer

y=3x+0

#### Work Step by Step

m=$\frac{y_2-y_1}{x_2-x_1}$
m=$\frac{12-3}{4-1}$
m=3
y-y$_1$=m(x-x$_1$)
y-3=3(x-1)
y=3x-3+3
y=3x+0

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

y=3x+0

m=$\frac{y_2-y_1}{x_2-x_1}$
m=$\frac{12-3}{4-1}$
m=3
y-y$_1$=m(x-x$_1$)
y-3=3(x-1)
y=3x-3+3
y=3x+0

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.